Teori-Teori Psikologi Pendidikan dan Implikasinya dalam Pembelajaran di Madrasah (Kajian Integratif Berbasis Nilai-Nilai Pendidikan Islam) - Muchammad Syafii; Siti Rohimah (Lembaga Yasin AlSys, 2026)
The gap between established learning theories and their systematic and value-based implementation in the context of Islamic education indicates the need for an integrative study on the application of educational psychology in Indonesian madrasahs and Islamic schools. This article aims to analyze the theoretical foundations of five major theories of educational psychology, namely Behaviorism, Cognitivism, Constructivism, Humanism, and Social Learning Theory, identify their practical implications for learning, and formulate an integrative model that aligns scientific learning theories with Islamic educational principles. This study used a systematic literature review method by synthesizing national and international peer-reviewed publications from 2019 to 2025 obtained from Scopus, Web of Science, and SINTA-indexed Indonesian journals. The data were analyzed through a critical review of the main concepts, pedagogical implications, and relevance of Islamic educational values in each learning theory. The results of the review show that each theory provides a unique pedagogical contribution, yet remains partial when applied separately. The five theories have conceptual compatibility with classical Islamic pedagogy, such as ta‘wid, tafakkur, halaqah, fitrah, and uswah hasanah. The formulated integrative model shows that combining various learning theories within the framework of Islamic values can create a holistic, meaningful, reflective, and character-building learning environment. This review contributes to the development of a conceptual framework for Islamic educational psychology and provides practical implications for madrasah and Islamic school educators in applying an eclectic-reflective approach that contextually integrates scientific learning theories with Islamic pedagogical traditions.